2016
DOI: 10.1073/pnas.1602878113
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-mechanical pushing of proteins along single-stranded DNA

Abstract: Single-stranded (ss)DNA binding (SSB) proteins bind with high affinity to ssDNA generated during DNA replication, recombination, and repair; however, these SSBs must eventually be displaced from or reorganized along the ssDNA. One potential mechanism for reorganization is for an ssDNA translocase (ATP-dependent motor) to push the SSB along ssDNA. Here we use single molecule total internal reflection fluorescence microscopy to detect such pushing events. When Cy5-labeled Escherichia coli (Ec) SSB is bound to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 69 publications
7
62
1
Order By: Relevance
“…Recent studies have shown that S. cerevisiae Pif1, and the E. coli UvrD and Rep helicases can push isolated E. coli SSB tetramers along ssDNA (Sokoloski et al, 2016). However, it remained unclear how helicases might behave when the ssDNA is fully coated by single strand binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that S. cerevisiae Pif1, and the E. coli UvrD and Rep helicases can push isolated E. coli SSB tetramers along ssDNA (Sokoloski et al, 2016). However, it remained unclear how helicases might behave when the ssDNA is fully coated by single strand binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Its ATPdependent activities include translocation along single-stranded (ss) DNA (12)(13)(14)(15)(16), duplex DNA unwinding (17)(18)(19)(20)(21)(22), displacement of RecA filaments from ssDNA (10,11), and pushing of proteins along ssDNA (23).…”
mentioning
confidence: 99%
“…For instance, smFRET studies have shown that SSB can diffuse along ssDNA, and this process may be involved in the displacement of SSB from ssDNA during the assembly of the RecA presynaptic complex 80 . SSB can even be pushed along ssDNA through the action of the E. coli helicases Rep and UvrD, which suggests a role for these helicases in assisting the reorganization or removal of SSB from DNA repair intermediates 81 . A TIRFM study looking at time-resolved widefield images of SSB bound to ssDNA revealed that SSB can form reversible long-range contacts that can lead to extensive condensation of SSB-bound ssDNA intermediates 82 .…”
Section: Sm-based Insights Into Recombinationmentioning
confidence: 99%